Effects of TiO2 sources on crystalline phase and morphology of BaTiO3 nanoparticles prepared via wet chemical route - Ziyi Liu; Juanjuan Xing; Shuanglong Yuan; Hua Tong (Materials Research Express)
Barium titanate (BaTiO _3 ) nanoparticles were synthesized via a hydrothermal method using barium hydroxide (Ba(OH) _2 ) and titanium oxide (TiO _2 ) as starting materials. The present study investigates the influence of TiO _2 sources on BaTiO _3 nanoparticle crystallinity and morphology. A comprehensive statistical analysis was conducted, revealing a direct correlation between the phase and size of the TiO _2 and the properties of the BaTiO _3 . Anatase TiO _2 , with a size ranging from 5–30 nm, was found to yield uniform spherical BaTiO _3 nanoparticles with sizes ranging from 66.1 ± 9.4 nm to 80.3 ± 10.8 nm. Conversely, rutile TiO _2 , with a size of 10 nm, yielded irregular particles with an average size of 386.6 ± 146.99 nm. XRD analysis demonstrated that smaller anatase TiO _2 (5 nm) exhibited a propensity to favor cubic-phase BaTiO _3 , while larger anatase TiO _2 (10–30 nm) exhibited a propensity to promote tetragonal-phase dominance. Conversely, rutile-derived BaTiO _3 exhibited a mixed phase (tetragonal-to-cubic ratio: 2:3). Kinetic studies of precursor synthesis have demonstrated that 5 nm anatase TiO _2 facilitates the rapid nucleation of BaTiO _3 within 30 s, reaching full conversion. This is in contrast to the slower kinetics caused by larger anatase TiO _2 and the negligible reactivity observed for rutile TiO _2 . These findings underscore the critical role of TiO _2 phase and size in tailoring BaTiO _3 nanoparticles for advanced dielectric applications, enabling precise control over particle size (60–80 nm) and crystallinity through precursor engineering.